2007
DOI: 10.1016/j.resp.2006.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Major differences in the pulmonary circulation between birds and mammals

Abstract: The lungs of domestic chickens were perfused with blood or dextran/saline and the pulmonary artery pressure (Pa) and venous pressure (Pv) were varied in relation to air capillary pressure (PA). In zone 3 conditions, pulmonary vascular resistance (PVR) was virtually unchanged with increases in either Pa or Pv. This is very different from mammals where the same interventions greatly reduce PVR. In zone 2 conditions blood flow was essentially independent of Pv as in mammalian lungs but all the capillaries appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 28 publications
0
37
1
Order By: Relevance
“…A little later, Powell et al (1985) showed that in contrast to the mammalian lung, where the pulmonary vascular resistance (PVR) decreases as cardiac output increases, owing mainly to the distension and recruitment of the BCs (Borst et al 1956;Glazier et al 1969), in the avian lung, PVR doubled after ligation (occlusion) of the left pulmonary artery, an experimental procedure that doubled the flow of blood to the right lung: the investigators concluded that 'the BCs are noncompliant'. The exceptional strength of the ACs and the BCs has now been corroborated by other investigators (Wideman, 2001;West et al 2006West et al , 2007aWideman et al 2007;Watson et al 2008). West et al (2007a) and Watson et al (2008) observed that 'the avian pulmonary BCs behave like rigid tubes that defy either expansion or compression'.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…A little later, Powell et al (1985) showed that in contrast to the mammalian lung, where the pulmonary vascular resistance (PVR) decreases as cardiac output increases, owing mainly to the distension and recruitment of the BCs (Borst et al 1956;Glazier et al 1969), in the avian lung, PVR doubled after ligation (occlusion) of the left pulmonary artery, an experimental procedure that doubled the flow of blood to the right lung: the investigators concluded that 'the BCs are noncompliant'. The exceptional strength of the ACs and the BCs has now been corroborated by other investigators (Wideman, 2001;West et al 2006West et al , 2007aWideman et al 2007;Watson et al 2008). West et al (2007a) and Watson et al (2008) observed that 'the avian pulmonary BCs behave like rigid tubes that defy either expansion or compression'.…”
Section: Introductionmentioning
confidence: 57%
“…Although accounts on the remarkable strengths of the ACs and the blood capillaries (BCs) of the avian lung have been in the scientific domain for about three decades (Macklem et al 1979;Powell et al 1985), until recently, only cursory references and speculations existed on this interesting property, which has now been sufficiently corroborated by, for example, Wideman (2001), West et al (2007a), and Watson et al (2008). The particular structures and ⁄ or mechanisms that can explain this property have remained obscure and contentious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…contribute to and explain the exceptional strength that has been reported in the avian lung by Macklem et al (1979), Powell et al (1985), and West et al (2007). The structural proximity between the lungs of the Ostrich, a bird from a taxon (ratite) considered to be the most primitive among birds (King and Farner, 1969;Storer, 1971a,b;Calder and Dawson, 1978), with those of the passerine birds (the most derived avian taxon) (Sibley and Alhquist, 1990;Barker et al, 2004), shows exceptional respiratory refinements for a nonvolant, supposedly primitive bird.…”
Section: Computer Reconstruction Of Parabronchus Of Ostrichmentioning
confidence: 81%
“…The pulmonary circulation receives the entire cardiac output but has a pressure approximately onefifth that of the systemic circulation, a figure that is remarkably consistent across mammalian species. 9 The relation- Figure 1. Morphological changes in an athlete's heart compared with a nonathlete's heart.…”
Section: Introductionmentioning
confidence: 99%